Time, expectations and financial markets - Hansjörg Herr (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2009)
After the breakdown of the Bretton Woods system and the beginning of the neoliberal revolution, financial markets became very unstable. The theoretical background of the neoliberal revolution stands in the tradition of Léon Walras. He was very much impressed by Isaac Newton, used his methodology and wanted to lift economic thinking on the same level as Newton's mechanics. The rational expectation approach and the hypothesis of efficient financial markets follow this methodology. In a Keynesian-Schumpeterian approach, expectations cannot be explained by economic models - as in the case of rational expectations. The economy is not a self-regulating stable system. Development depends on social and political processes which are beyond the scope of narrow economic modelling. The world needs a fundamental re-regulation of asset and financial markets as well as labour markets to turn globalisation into a project with more winners than there are now.
Keywords: B22; E12; E22; 330; Macroeconomics; Post-Keynesian; Financial Markets and the Macroeconomy